2013
DOI: 10.5194/bg-10-3055-2013
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations of virus- and nanoflagellate-mediated mortality of heterotrophic bacteria in the coastal ecosystem of subtropical western Pacific

Abstract: Since viral lysis and nanoflagellate grazing differ in their impact on the aquatic food web, it is important to assess the relative importance of both bacterial mortality factors. In this study, an adapted version of the modified dilution method was applied to simultaneously estimate the impact of both virus and nanoflagellate grazing on the mortality of heterotrophic bacteria. A series of experiments was conducted monthly from April to December 2011 and April to October 2012. The growth rates of bacteria we m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 67 publications
2
38
0
2
Order By: Relevance
“…A subset of this effort has been devoted to assessing the role of viruses and protists in bacterial mortality. Predation on bacteria in marine, estuarine and freshwater systems has been the subject of many studies in the past two decades (Proctor and Fuhrman 1990;Fuhrman and Noble 1995;Weinbauer and Höfle, 1998;Tsai et al, 2013), prompted largely by the report of Proctor and Fuhrman (1990) that there are 10 6 viruses per ml of seawater in the world's oceans. These studies have shown viruses to be major causative agents of bacterial mortality, sometimes exceeding the importance and activity of protistan grazers in aquatic systems.…”
Section: Introductionmentioning
confidence: 99%
“…A subset of this effort has been devoted to assessing the role of viruses and protists in bacterial mortality. Predation on bacteria in marine, estuarine and freshwater systems has been the subject of many studies in the past two decades (Proctor and Fuhrman 1990;Fuhrman and Noble 1995;Weinbauer and Höfle, 1998;Tsai et al, 2013), prompted largely by the report of Proctor and Fuhrman (1990) that there are 10 6 viruses per ml of seawater in the world's oceans. These studies have shown viruses to be major causative agents of bacterial mortality, sometimes exceeding the importance and activity of protistan grazers in aquatic systems.…”
Section: Introductionmentioning
confidence: 99%
“…4), because it modifies the export flux and its chemical composition. Hung et al (2013) uses a resuspension model, which is able to provide an estimate of the resuspended fraction collected in sediment traps. This fraction amounts from 27 to 93 % of the total flux.…”
Section: Regional Biogeochemical Processesmentioning
confidence: 70%
“…Schematic diagram showing the major biogeochemical features in the river-shelf-boundary current systems observed in studies of this special issue. Riverine nutrients-induced phytoplankton bloom in the river plume draws down pCO 2 and produces high particulate organic carbon (POC) flux (Hung et al, 2013), which causes strong community respiration probably driven by active resuspension (Hung et al, 2013). The elevated particle concentrations near the river mouth sustain exceptionally high microbial activities, which include nitrification processes facilitated probably by the particle-borne metal oxides .…”
Section: Increasing Atmospheric Co 2 and Changing Carbonate Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…The modified dilution method (MDiM) (Evans et al, 2003;Kimmance and Brussaard, 2010) is used to quantify the impact of both grazing and viral lysis on microbial populations. Empirical measurements made via the MDiM suggest that both grazing and viral lysis are important mortality drivers of marine microbes; and that both can be the dominant source of mortality (Tsai et al, 2013;Mojica et al, 2015;Pasulka et al, 2015). Yet, the MDiM can yield negative rates of viral lysis (Pasulka et al, 2015) and there are concerns about the ability to detect viral impact e.g.…”
Section: Introductionmentioning
confidence: 99%